O papel da managerial discretion na gest??o dos executivos sobre o desempenho organizacional - Sierra, J??lio Cesar Volpp (2019)
Strategy researchers have always focused on identifying the background to organizational performance, with one of their main focuses being the relationship between executives, the constraints imposed, and the latitude for action of these executives, targeting organizational results. The set of imposed constraints and latitude for action is called managerial discretion. This thesis is composed of three interdependent studies, with the objective of identifying which factors can influence the management of executives and, in turn, the performance of semiautonomous units in organizations that use this structural model. To do so, the first study aimed to delimit the state of the art of relevant scientific production, through bibliometric studies of couple pairing. The relevance of the topic was identified and the interest of the academy in researching the relation between the characteristics of the executives and the performance of the organizations was ascertained. The second, quantitative study, evaluated the relationship between managerial discretion and the performance of semiautonomous units of Brazilian commercial bank, with the main findings being the existence of managerial discretion and attesting that the restrictions and the latitude for action of the chief executives of these units are real. The third study, in turn, attempted to evaluate the effects of managerial discretion by comparing semiautonomous units in the same organization, with performances considered good and bad. The main theoretical contribution of this study as a whole relates to the proof of the existence of managerial discretion and its pillars in semiautonomous units, since until then it was restricted to levels of country and organization. From the managerial point of view, this study contributes to the demonstration of the relationships between the certain characteristics of the executives, the semiautonomous units and the markets in which these units are inserted. An adequate reading of these relationships can potentiate the generation of results in the units and in the organizations. This work, in turn, also addresses the possibility of future research in the three studies, regarding the scope expansion for bibliometric studies and test of new variables to confirm the relationships found in the test of the hypothesis of the empirical studies. It is also indicated that future studies advance in the tests that prove the moderating role of the managerial discretion in the action of the executives of semiautonomous units on the performance of these units.